The second hit: comorbidities in systemic lupus erythematosus. Issue 5 (October 2007) - Pineau, Christian A; Lee, Chin; Ramsey-Goldman, Rosalind; Clarke, Ann E; Bernatsky, Sasha
Patients with systemic lupus erythematosus (SLE) now benefit from an improved life expectancy. As this multisystem autoimmune disorder progressively became a chronic disease over the last few decades, we gradually realized that this more favorable prognosis came at a price: the occurrence of comorbidities. The main comorbidities recognized in SLE patients include cardiovascular disease, osteoporosis and malignancies. As these conditions now represent a significant proportion of the morbidity and mortality associated with SLE, it is important to understand them better in order to appropriately screen for them, or even to try preventing them. We will, in this article, review the current literature on these three complications, which can be an unfortunate ''second hit'' for patients suffering from an already complex illness.